CONCRETE WITH GLASS POWDER AND PLASTIC AS PARTIAL REPLACEMENT - Ritesh Jain. (International Journal of Modern Agriculture, 2021)
Studies on Glass powder (GP) and plastic incorporation in concrete and characteristics exhibited by mixtures prepared using different percentages have been carried out in the past and this review summarizes the studies carried out in the past decade and presents the current understanding in the area. It is aimed to make this review a source for future studies in this aspect. This study was performed in 3 different approaches, in first approach possible partial replacement by glass waste was studied, in second, partial replacement by plastic waste was studied and in third, replacement by both glass and plastic waste together was studied. Selective targeting of mechanical characteristics such as compressive strength, flexural strength, split tensile strength, modulus of elasticity was done in the article as they are the most important aspects which need to be considered. Using both glass powder and plastic waste together in concrete as a partial replacement show best as glass powder used in the mixture counters the adverse effects of plastic.